Institutional Quality, Industrial Policies, and Regional Specialization Dynamics in Morocco: What Levers for Inclusive and Territorialized Growth? - YAHYAOUI Rachid; TABAKKOUYAT Rachid (African Scientific Journal, 2025)
Abstract This study examines the interrelated roles of institutional quality, industrial policy, and regional specialization in promoting inclusive and territorially balanced economic growth in Morocco over the period 2010–2024. Using advanced panel econometric methods, including ARDL bounds testing, Pedroni and Westerlund cointegration analyses, and Pooled Mean Group (PMG) estimations, the research identifies a robust and stable long-run relationship among these variables across Moroccan regions. The findings reveal that institutional quality is the most significant driver of regional growth, while industrial policies contribute positively in both the short and long term. Regional specialization, although less influential in the short run, strengthens the long-term economic trajectory when embedded within institutional and policy frameworks. The results underscore the necessity of territorially sensitive policies and institutional reforms to foster regional convergence and economic inclusivity. The paper concludes with actionable policy recommendations to align regional governance, industrial development, and specialization strategies for sustained territorial growth. Keywords: Institutional Quality Global; Industrial Policy; Inclusive Growth; Panel ARDL.